Vocational School Student Entrepreneurship Strategy - Laila Lupita Ardhiyanti; Tri Kuat; Muhammad Sayuti (Universitas Ahmad Dahlan, 2023)
This study aims to analyze the strategies used by a successful vocational high school student in entrepreneurship. This research is a qualitative type of research with phenomenological research methods. This method approach uses the development of the Post-modern Phenomenology specification paradigm. Phenomenology is presented descriptively. Phenomenological research data collection was carried out using in-depth interview techniques. The results of this study reveal the strategies used by Ayu in the form of expanding the reach of promotions, forming networks, and paying attention to sales prices.